Marriage in Secret According to Islam and Catholic: A Comparative Study on Religious Laws - Tjatur Raharso, Alphonsus; Barak, Antonius (Department of Religious Studies, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2022)
This article discusses secret marriage from another perspective, namely in the form of a comparative study of religious law between Islam and Catholicism. This research aims to find similarities and differences between the two religions in assessing and regulating secret marriages. This study found that both religions recognize secret marriage as an uncommon and not ideal marriage. Both religions see the disadvantages and harms of secret marriage. This study found some key differences. In Islam, sirri marriage is not created by religious doctrine, but are practices carried out by several people which is subsequently judged and regulated by religious law. Whereas in Catholicism, secret marriage are officially created by the highest legislator of the Church. In Islam, unregistered marriage often colludes with polygamy, while in the Catholic Church secret marriage is carried out while upholding the essential nature of marriage: monogamous and indissoluble. In Islam, sirri marriage is not recorded anywhere, while secret marriage in the Catholic Church is recorded internally in the diocesan secret archives. This study raises mutual respect among adherents of both religions regarding secret marriages. This study also encourages further studies on the problem of the two religions facing civil lawsuits regarding marriage registration.